The Nutrition Awareness Family Education Movement (KADARZI) Towards An Independent Family For The People Of Jombok Village, Kec. Ngoro Jombang - Novita Nur Synthiawati; Ririn Febriyanti (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The Nutrition Awareness Family (KADARZI) is a government program implemented to address nutritional problems. Families are expected to be able to independently realize good nutritional conditions to improve the health of mothers and children and their entire families. This community service aims to provide education and assistance to create healthy, independent and nutrition-aware families. The problems faced by partners in Jombok Village, Ngoro District, include ( 1). Lack of understanding of Family Independence in this case is the development of adolescent character so that it has an impact on adolescent behavior and nutrition, (2). Young Marriage and divorce are relatively high in 2020 to 2021; 3) Lack of Knowledge about Good Parenting for Toddlers, Teenagers and Pregnant Women. The method used in this service program is 1). with an asset based community driven development approach through education and mentoring that leads to the context of understanding and internalizing assets, potential, strength and utilization independently and optimally; 2). Discussions in the form of questions and answers but more precisely sharing experiences on how to instill and develop character in adolescents as well as family nutritional development. The results of this dedication are 1). Increased understanding of the role of the family (father/mother) as the embodiment of a healthy, independent family and a nutrition-aware family, (2) Increased understanding of the mindset and parenting pattern as well as the problems faced by adolescents as the embodiment of a healthy, independent and stunting-free family.